THE IMPACT OF WORKING HOURS AND WORKLOAD ON HOTEL FOOD AND BEVERAGE STAFF’S HEALTH STATUS DURING COVID-19 PANDEMIC - Arnieyantie, A.H.; Norrina, D; Nur Alia Hanani, H; Mohamad Azli, R.; Noorliza, Z.; Hussin Khan, R.K. (International Journal of Accounting, Finance and Business, 2022)
The COVID-19 pandemic had a significant influence on several industries, particularly the hotel industry. The hotel's decision to reduce employee numbers as part of its survival strategy has had an impact on the surviving employees, including increased workload and excessive working hours. As a result, this study investigated the impact of working hours and workload on the health of hotel food and beverage workers during the COVID-19 epidemic. The quantitative approach using an online survey was applied throughout the study. The data were analyzed using Statistical Package for the Social Sciences (SPSS) version 20 after delivering a questionnaire to 100 respondents. Only one of the two independent factors evaluated has a significant (p<0.05) impact on the health of hotel food and beverage employees. Workload influences the health of hotel food and beverage employees, according to the study. Based on the findings, management should prioritize job distribution by stressing work delegation according to the job description, job schedule, task SOP, and teamwork among employees to reduce workload and prevent health problems among hotel food and beverage employees.